Exploring the Medication Patterns of Professor Zulong Wang in Treating Sleep-Related Painful Erection Based on Data Mining - Zhao, Hanbin; Ma, Miaomiao; Li, Yuanyuan; Wang, Guangzhao; Zhu, Wenbo; Wang, Zulong (Chinese medicine and natural products, 2025)
To explore the medication patterns of Professor Zulong Wang in treating sleep-related painful erection (SRPE) through data mining, aiming to discover new therapeutic strategies for traditional Chinese medicine in managing this condition.Medical records of SRPE patients treated by Professor Zulong Wang at the First Affiliated Hospital of Henan University of Chinese Medicine from February 2021 to December 2024 were collected to establish a database. Frequency analysis, association rule analysis, and cluster analysis were employed to examine the frequency of herb use, four properties and five flavors, channel tropisms, and herb combinations.A total of 59 prescriptions meeting the criteria were included, involving 81 Chinese herbs, among which 27 herbs were used 10 or more times. The primary herb properties were cold, warm, and neutral, with bitter, sweet, and pungent flavors being most common. The herbs predominantly entered the liver, heart, spleen, and kidney channels. Forty-three commonly used herb combinations were identified, and cluster analysis revealed six core herb groups.Professor Zulong Wang primarily treats SRPE with modified Huoluo Xiaoling Dan, focusing on unblocking collaterals and relieving pain, supplemented by soothing the liver and regulating qi, resolving stasis and phlegm, nourishing yin and reducing fire, and tonifying the kidney and activating blood circulation.
Keywords: sleep-related painful erection; medication patterns; Huoluo Xiaoling Dan; unblocking collaterals and relieving pain; Zulong Wang; traditional Chinese medicine